VERIFIKASI KARTU MENUJU SEJAHTERA (KMS) MENGGUNAKAN SISTEM PENDUKUNG KEPUTUSAN BERBASIS WEB DESA DUTOHE KECAMATAN KABILA - Sulistiawati Rahayu Ahmad (Universitas PGRI Semarang, 2019)
Kartu Menuju Sehat is part of a government program in the context of handling poverty that is always updated every year receiving data, so that assistance reaches the hands of the poor, the data collection of families must be as expected, although many parameters / indicators of poverty result in less effective poverty management programs. The results of the analysis of the data of poor families after re-verification conducted by Dutohe Village, Kabila Subdistrict, Bone Bolango District, showed that the cause of the misidentification of poor families was due to errors during the data collection process, errors in the calculation process, and due to fraud during the data collection. This study designed a decision support system using the Technique For Others Reference Method by Similarity to Ideal Solution (TOPSIS) in the Verification process Kartu Menuju Sehat (KMS) in order to produce the right and accurate decision making that involves the privacy value or preference value of the KMS recipient. The results showed an increase in terms of effectiveness and efficiency in card verification processing